Aplikasi Teknologi Virtual Reality (VR) dalam Pembelajaran : Sebuah Studi Literatur - Zahriah; Fera Annisa; T. Murdani Saputra; Marlisa Rahmi; Najwa Fitria (Bansigom Na Publisher, 2025)
Virtual Reality (VR) technology has become one of the innovative solutions that offers immersive and interactive learning experiences, but its implementation still faces various challenges. This research aims to examine the development, implementation and impact of using VR in learning based on an analysis of 28 scientific articles published in national journals during the 2020–2024 period. This research uses a systematic literature review method by analyzing articles related to VR applications in learning at primary, secondary and tertiary levels. The articles analyzed include the development of VR-based content, the implementation of VR media, as well as evaluating its impact on the quality of learning. The research results show that VR has been successfully applied in various fields of study, from science, history, to practical simulations such as the Hajj and microteaching. VR technology is proven to increase motivation, concept understanding, student engagement, and learning outcomes. However, VR implementation also faces challenges such as high costs, special training requirements, and limited technological infrastructure. Thus, these findings confirm the potential of VR technology as a significant learning innovation in improving the quality of education, although strategies are needed to overcome barriers to its implementation.